MODELING STOCHASTIC INTEREST RATE IN LIFE CONTINGENCIES - Lienda Noviyanti; Muhammad Syamsuddin (Program Studi Statistika Unisba, 2004)
In this paper we model stochastic interest rate in life contingencies through a simulation. In addition, some risk measuresare employed to measure the risk of interest rate fluctuation which based on loss function.